Indoleamine 2,3-dioxygenase 1-mediated immune suppressive status is positively associated with brain metastasis in patients with non-small cell lung cancer - Weiwei Chen; Li Yang; Victor Ho-fun Lee; Liangliang Xu; Lingyu Ma; Zhenghao Ye; Wanli Xu; Caining Zhao; Danyang Zheng; Karrie Mei-Yee Kiang; Stella Sun; Yuan Qu; et al. (Journal of the National Cancer Center)
Background: Indoleamine 2,3-dioxygenase (IDO1) activity, measured by kynurenine/tryptophan (K:T) ratio, is known for its association with distant metastasis and overall survival (OS) in patients with non-small cell lung cancer (NSCLC). Here, we aimed to examine whether IDO1 activity is correlated with OS in NSCLC patients with brain metastasis (Bramet) and has negative effect on modulating the anti-tumor functions of immune cells. Methods: This study was a part of a prospective clinical trial in circulating biomarkers. Blood or tissues from eligible participants were collected for measurement of kynurenine, tryptophan, immune cell subtype, scRNA-seq analysis, and untargeted metabolomics analysis. Results: A total of 195 patients were enrolled. The median kynurenine to tryptophan (K:T) ratio was 0.18, with consistent values observed among patients with NSCLC Bramet and those without (0.18 and 0.11, respectively). Notably, student's t-test analysis revealed significantly higher kynurenine concentrations in stage IV patients compared to those in stage I (2.3 vs 1.7 µM, P < 0.001). In patients with Bramet, both kynurenine concentrations and K:T ratios were significantly elevated in comparison with those of extra-cerebral metastasis (2.7 vs 1.9 µM, P < 0.001; 0.12 vs 0.095, P = 0.028; respectively). Single-cell analysis further validated a high level of IDO1 expression in stage IV tumors or Bramet lesions, particularly in macrophages, regulated by chemokines such as CXCL11. Additionally, K:T ratios exhibited significant associations with Treg cell percentages and OS in patients with Bramet (P = 0.039). Treatment with kynurenine led to the upregulation of immune-suppressive molecules, including PD-1, in T cells. Finally, untargeted metabolomics analysis further identified that, apart from the IDO1 metabolic pathway, other metabolites, such as those involved in phospholipid pathways, were also implicated in Bramet. Conclusion: IDO1 metabolites may play immune-suppressive roles in NSCLC patients with Bramet.